The Effectiveness of VocabARy Web-AR as English Learning Media for Students of SMP Negeri 3 Wonosalam - Ubaidillah Ube; Iin Baroroh Ma'arif (Journal of English Language Learning, 2026)
This study investigates the effectiveness of VocabARy, a Web-based Augmented Reality (Web-AR) platform, in enhancing students’ English vocabulary mastery. The research employed a mixed-methods sequential explanatory design involving 26 eighth-grade students at SMP Negeri 3 Wonosalam Jombang. Quantitative data were collected through pre-test and post-test, while qualitative data were obtained from questionnaires, interviews, and observations. The findings revealed a significant improvement in students’ vocabulary mastery. The mean score increased from 26.61 in the pre-test to 80.73 in the post-test, with a standard deviation decrease from 9.52 to 7.58, indicating more consistent performance. The paired sample t-test showed a statistically significant difference (p < 0.01), confirming the effectiveness of the intervention. Furthermore, the N-Gain score reached 0.7454 (high category), demonstrating substantial learning improvement. Qualitative findings indicated that students perceived VocabARy as useful, easy to use, and motivating. The integration of Web-AR technology provides an interactive and engaging learning experience. Therefore, VocabARy is considered an effective and innovative tool for vocabulary learning in EFL contexts.